Trawling bats exploit an echo-acoustic ground effect - Zsebok, Sandor; Kroll, Ferdinand; Heinrich, Melina; Genzel, Daria; Siemers, Bjoern M.; Wiegrebe, Lutz (Frontiers in Physiology, 2013)
A water surface acts not only as an optic mirror but also as an acoustic mirror. Echolocation calls emitted by bats at low heights above water are reflected away from the bat, and hence the background clutter is reduced. Moreover, targets on the surface create an enhanced echo. Here, we formally quantified the effect of the substrate and target height on both target detection and –discrimination in a combined laboratory and field approach with Myotis daubentonii. In a two-alternative, forced-choice paradigm, the bats had to detect a mealworm and discriminate it from an inedible dummy (20 mm PVC disc). Psychophysical performance was measured as a function of height above either smooth substrates (water or PVC) or above a clutter substrate (artificial grass). At low heights above the clutter substrate (10, 20 or 35 cm), the bats’ detection performance was worse than above a smooth substrate. At a height of 50 cm, the substrate structure had no influence on target detection. Above the clutter surface, also target discrimination was significantly impaired with decreasing target height. A detailed analysis of the bats’ echolocation calls during target approach shows that above the clutter substrate, the bats produce calls with significantly higher peak frequency. Flight-path reconstruction revealed that the bats attacked an object from below over water but from above over a clutter substrate. These results are consistent with the hypothesis that trawling bats exploit an echo-acoustic ground effect, in terms of a spatio-temporal integration of direct reflections with indirect reflections from the water surface, to optimize prey detection and –discrimination not only for prey on the water but also for some range above.